THE IMPORTANCE OF “AT-TABAQAT AL-KUBRA” IN THE STUDY OF ISLAMIC BIOGRAPHIES - Sotvoldiev Oybek Khayrullo ogli (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information about the importance of the work “al-Tabaqat al-Kubra” by Muhammad ibn Sa’d as a biographical source. Ibn Sa’d was a historian lived in the Abbasid era. The work consists of 5554 persons’ biographies (with repetitions) in total and studies them in classes. The article reveals the content of these classes.